2012
DOI: 10.1063/1.4730578
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative validation of an air-coupled ultrasonic probe model by Interferometric laser tomography

Abstract: The present paper describes the quantitative validation of a finite element (FE) model of the ultrasound beam generated by an air coupled non-contact ultrasound transducer. The model boundary conditions are given by vibration velocities measured by laser vibrometry on the probe membrane. The proposed validation method is based on the comparison between the simulated 3D pressure field and the pressure data measured with interferometric laser tomography technique. The model details and the experimental technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Numerical methods are used to model and validate the influence of transducer material designs in excited ACU pressure fields, the interaction of ACU pressure fields with light sources, or the propagation of excited ACU beams in solid objects for NDE, among others. Popular methods are the finite element method (FEM) [17,[21][22][23] and finite-difference timedomain analysis (FDTD) [24,25]. While these methods are very flexible, they require a discretization of the full wave propagation domain and discretization steps h of at least one order of magnitude smaller than the wavelength , with typically h< /20.…”
mentioning
confidence: 99%
“…Numerical methods are used to model and validate the influence of transducer material designs in excited ACU pressure fields, the interaction of ACU pressure fields with light sources, or the propagation of excited ACU beams in solid objects for NDE, among others. Popular methods are the finite element method (FEM) [17,[21][22][23] and finite-difference timedomain analysis (FDTD) [24,25]. While these methods are very flexible, they require a discretization of the full wave propagation domain and discretization steps h of at least one order of magnitude smaller than the wavelength , with typically h< /20.…”
mentioning
confidence: 99%
“…The calculation of instantaneous sound pressure using light intensity measurements has been shown to be sensitive and accurate [4]. The use of laser Doppler vibrometry to measure pressure fluctuations has received significant attention [5][6][7][8][9][10][11][12], including tomographic 3D field reconstruction [13][14][15][16][17]. Previous research has shown that quantified sound field visualisation is possible but the implementation is relatively complex.…”
Section: Introductionmentioning
confidence: 99%